2020
DOI: 10.1111/bpa.12891
|View full text |Cite
|
Sign up to set email alerts
|

Medullary tyrosine hydroxylase catecholaminergic neuronal populations in sudden unexpected death in epilepsy

Abstract: Sudden unexpected death in epilepsy (SUDEP) is mechanistically complex and one probable cause is seizure‐related respiratory dysfunction. Medullary respiratory regulatory nuclei include the pre‐Bötzinger complex (pre‐BötC) in the ventrolateral medulla (VLM), the medullary raphé nuclei (MR) and nucleus of solitary tract in the dorsomedial medulla (DMM). The region of the VLM also contains intermingled tyrosine hydroxylase (TH) catecholaminergic neurones which directly project to the pre‐BötC and regulate breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…One theory of the cause of sudden unexpected death in epilepsy (SUDEP) proposes that a central, irrecoverable failure of autonomic regulation of cardiovascular and respiratory function occurs around the time of a seizure. In previous postmortem (PM) studies we have identified alterations to selective neuronal and glial populations in medullary respiratory regulatory nuclei in SUDEP, 1‐3 suggesting preexisting pathology, possibly secondary to previous seizures or episodes of seizure‐related hypoxia. In a PM pathology‐MRI (magnetic resonance imaging) correlative study we also observed volume reduction in the rostral medulla in SUDEP, 4 in keeping with in vivo MRI studies 5,6 and in support of regional alterations.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…One theory of the cause of sudden unexpected death in epilepsy (SUDEP) proposes that a central, irrecoverable failure of autonomic regulation of cardiovascular and respiratory function occurs around the time of a seizure. In previous postmortem (PM) studies we have identified alterations to selective neuronal and glial populations in medullary respiratory regulatory nuclei in SUDEP, 1‐3 suggesting preexisting pathology, possibly secondary to previous seizures or episodes of seizure‐related hypoxia. In a PM pathology‐MRI (magnetic resonance imaging) correlative study we also observed volume reduction in the rostral medulla in SUDEP, 4 in keeping with in vivo MRI studies 5,6 and in support of regional alterations.…”
Section: Introductionmentioning
confidence: 89%
“…This study was underpowered to detect regional differences in SUDEP cases with recent seizures compared to epilepsy controls; however, further studies of regional microglia responses and activation states in response to seizures are clearly warranted in SUDEP. In previous studies in SUDEP, we have recognized regional alteration in neuromodulators, including neuropeptidergic, adenosine, catecholaminergic, and serotonergic systems, [1][2][3]30,32 which may reflect network changes; as these neuromodulators also regulate microglial cells and their activation, 33 it is not inconceivable that these processes are inter-related. Activated microglial cells are also known to be increased in focal epilepsy pathologies, as focal cortical dysplasia, and correlate with duration of epilepsy, 34 with evidence of regional localization of the inflammation on C 11 PK11195 PET.…”
Section: Microglial Responses In Epilepsymentioning
confidence: 99%
“…In addition to parallels in mechanism of death in SUDC and SUDEP [ 27 , 28 , 37 , 49 ], altered serotonergic signaling in brainstem and other regions is postulated to contribute to SUDEP risk [ 43 , 51 , 55 58 ]. We evaluated the same brain regions in SUDEP, but did not identify differences [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two additional studies found no differences between PWE and SUDEP with several markers in medullary regions. 35 , 36 Whole exome sequencing in surgical brain tissue from epilepsy patients that died from SUDEP implicate several gene variants that may increase risk of SUDEP. 58 , 59 We recently identified a number of protein differences between epilepsy and non-epilepsy control cases by localized proteomics in cortex and hippocampal CA1-3 and DG, 60 however found no significant protein differences when comparing SUDEP to epilepsy and few differences in the hippocampus of high-risk SUDEP MTLE cases with a prolonged PGES by RNAseq.…”
Section: Discussionmentioning
confidence: 99%